Creatively connecting science, society and the sea: a mini-review of academic literature focusing on art-science collaborations and the ocean - Whittaker, Geraint Rhys (Frontiers in Marine Science, 2023)
Collaborations between artists and ocean scientists are becoming increasingly frequent. As the UN Ocean Decade (2021-2030) stresses the importance of engaging with the public, there is a growing interest in using art as a tool for communication as well as for scientific exploration and experimentation. This mini-review charts the current academic research on art-science collaborations and the ocean, focusing on literature where artists and scientists work together to produce something based on scientific research. The study finds that these relationships are never apolitical, are complex and develop differently depending on each project. In sum the paper will highlight that although the academic literature is limited, its diversity has the potential to reach numerous academic disciplines and that focusing on process and engagement should be a direction for further research to help broaden the academic reach of these important oceanic knowledges.